Non-Hermitian d-dimensional Hamiltonians with position-dependent mass and their η-pseudo-Hermiticity generators - Mustafa, Omar; Mazharimousavi, Habib S. (Springer, 2006)
A class of non-Hermitian d-dimensional Hamiltonians with position-dependent mass and their η-pseudo-Hermiticity generators is presented. Illustrative examples are given in 1D, 2D, and 3D for different position-dependent mass settings.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: η-pseudo-Hermiticity, Position-dependent mass; Non-Hermitian Hamiltonians; d-dimensional Hamiltonians